Mexico City—Ambitions and Challenges of Integrated Risk Management in a Fractured Urban Planning Context - Soledad Garcia Ferrari; Emma R. Morales; Amelia A. Bain (Earth Science, Systems and Society)
Among the growing number of megacities, Mexico City stands out for its size and population, but also for its challenges with respect to environmental risk management, fractured governance and marked contrasts in urban conditions. In the last couple of decades, Mexico City has been praised for pioneering new management structures for planning and policy development, driving an approach rooted in a strong social commitment and sustainability agenda, with more integrated decision-making across government institutions. Among these instruments is the recent Law of Integrated Risk Management and Civil Protection of Mexico City, which boldly steps ahead of national legislation, moving from a reactive to a precautionary approach to disaster risk under the banner of stakeholder co-responsibility. However, this paper shows that Mexico City has also been the stage of innovative policies that have been hijacked by the powerful, tainted by corruption and reinterpreted to fit financial interests, or simply abandoned with the arrival of new administrations. The efficiency of these innovative strategies has therefore thus far been limited by discretionary practices and poor communication and socialisation. Our research over the past 5 years has explored risk management processes in Mexico and Mexico City through a transdisciplinary investigation of the vulnerability to climate change-related hydro-meteorological risks in low-income urban areas, and the capacities to manage risk at the community and institutional levels. Drawing on this research, this paper describes a range of accomplishments in urban and environmental policy innovation in Mexico City in recent years with relevance to risk management, and the opportunities for learning arising from the challenges, limitations, and failures. The paper argues that, despite extensive existing knowledge of the socio-technical elements of risk in the city, in particular in relation to hydro-meteorological and seismic risks, fragmented urban development policies and institutions have contributed to increasing the vulnerability of poor communities in high-risk areas of the city. The paper concludes that addressing the challenges of integrated risk management in this fractured urban planning context will require that the recently-created institutions are adaptive, to cope with evolving socio-economic contexts and physical hazards, build strong links with academia to harness social and technical knowledge, design long-term plans integrated across tiers of government to increase coordination, and generate strong and inclusive engagement of the city’s heterogeneous communities. These elements are crucial to allow Mexico City’s ambitions of integrated risk management to survive political cycles and avoid appropriation by short-term financial interests over real risk reduction.